Förekomst av Lawsonia intracellularis och Brachyspira spp. hos häst i Sverige - Johansson, Ted (2006)
Proliferative enteropathy (PE) caused by Lawsonia intracellularis has been reported in horses in the USA, Canada, Australia and Great Britain. Diarrhoea caused by Brachyspira antigen-containing spirochaetes has been diagnosed in a horse in Japan. The presence of Lawsonia intracellularis or Brachyspira spp. have neither been investigated in healthy nor in sick horses in Sweden. The purpose of this study was to survey the occurrence of the two bacteria in Swedish horses. Faecal samples were gathered from 108 foals without any clinical signs of illness in the age of four to eight months. The samples were collected from four different stud farms. A nested PCR was used to detect Lawsonia intracellularis and culture was used to detect the presence of Brachyspira spp. In this study neither of the two bacteria were found. The explanations for the result might be that the bacteria do not exist in the Swedish horse population, or that they do not exist in horses from the examined area or that the horses did not shed a detectable number of bacteria.